Robotic Arm Control using Internet of Things (IoT) - Badrul Hisham, Amirah ‘Aisha; Low, Zi Han; Ishak, Mohamad Hafis Izran; Idris, Nurul Hawani (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Robotic arm is a reprogrammable and multifunctional manipulator design to assist human in various surroundings. It is able to overcome human inefficiency in performing repetitive task such as pick and place operation. Thus, industrial in assembly and manufacturing have widely integrated robotic arm into their assembling line to overcome the problem of human inefficiency. Internet of things (IoT) allow data to be exchange between devices through the connection of many devices. The integration of internet of things with robotic arm allows smart industry to be realized. The purpose of this research is to design and build a three degree of freedom robotic arm with a mechanical gripper. The robotic arm can be controlled remotely through android mobile device to perform pick and place operation while Matlab provides the graphical movement of the robotic arm as a feedback.